2017
DOI: 10.1097/gme.0000000000000755
|View full text |Cite
|
Sign up to set email alerts
|

Aging ovary and the role for advanced glycation end products

Abstract: Further investigation of the role for the AGE-RAGE axis in the ovarian follicular environment is needed, and results could relate to assisted reproduction technology outcomes and new measures of ovarian reserve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 74 publications
0
25
0
Order By: Relevance
“…Other studies have shown that the follicular fluid of aged women has lower glutathione peroxidase and superoxide dismutase levels [102,103]. Advanced glycation end products (AGEs) are also closely related to declining ovarian function as the accumulation of AGEs contributes directly to protein damage, induces a chain of oxidative stress reactions, and increases inflammatory reactions, thereby inducing a premature decline in ovarian function [104,105]. The external environment may affect aging by regulating key metabolic sensors (e.g., SIRT1 and AMPK), which interact with the mammalian target of rapamycin and insulin/insulin-like growth factor 1 (IGF-1) to control energy metabolism and cell growth.…”
Section: Aging Causes Metabolic Disorders In the Ovariesmentioning
confidence: 99%
“…Other studies have shown that the follicular fluid of aged women has lower glutathione peroxidase and superoxide dismutase levels [102,103]. Advanced glycation end products (AGEs) are also closely related to declining ovarian function as the accumulation of AGEs contributes directly to protein damage, induces a chain of oxidative stress reactions, and increases inflammatory reactions, thereby inducing a premature decline in ovarian function [104,105]. The external environment may affect aging by regulating key metabolic sensors (e.g., SIRT1 and AMPK), which interact with the mammalian target of rapamycin and insulin/insulin-like growth factor 1 (IGF-1) to control energy metabolism and cell growth.…”
Section: Aging Causes Metabolic Disorders In the Ovariesmentioning
confidence: 99%
“…This decline has various causes. For instance, it can result from oxidative stress along with glycation processes [ 5 ] or mitochondrial aging. [ 6 ] Epigenetic alterations are also expected to have an impact on ovarian aging.…”
Section: Figurementioning
confidence: 99%
“…The human female reproductive axis typically declines quickly in women after the age of 35. Since, as in other organs, free radical damage contributes to diminished reproductive processes including the onset of menopause [203,204], the antioxidant melatonin has been tested for its potential in deferring the slowed follicular maturation and reduced oocyte quality observed in the aging female. The results of these studies verify that melatonin has significant benefits in maintaining the function of the ovary and adnexa which normally deteriorates with age or after exposure to toxins, etc.…”
Section: The Melatonin/sirt3 Interactionsmentioning
confidence: 99%